CLÍNICA PSICANALÍTICA: O SENTIMENTO DE SOLIDÃO E A SAÚDE MENTAL DE MULHERES CASADAS - Rossi, Fernanda Costa Luz (2006)
This present work had as a main objective to investigate the feeling of loneliness and mental health of married women by comparing both ways of understanding and experiencing this feeling between single and married women as well as to verify how this emotion can be mitigated thorough the presence of a partner in a marriage (cohabitation) and also the conditions in which it would happen. We started from the hypothesis that this sentiment is shared by everybody, once human being is unique and individual. Thus, the eternal separation from the other, which starts when the baby realizes that he is different from the mother, consequently, a unique individual, is associated to a sensation of which accompanies the human being throughout his life. Therefore, it is very common to observe people getting involved in relationships in order to minimize this feeling, which in turn, gets stronger and each passing day to the superficiality of emotional bondings. The presence of another person can be an advantage in an interpersonal relationship when the intensity of the hostility decreases added by the feeling of solitude. The antidote against this sentiment comes from strengthening self knowledge, autonomy and from the friendship of a companion who shows unconditional acceptance by the true self. For this reason, a quantitative and qualitative study using undergraduate single women was carried out in order to analyze this sentiment in married women. The sample was randomized and grouped in three phases. 184 women, 38% married, 7,6% divorced and 52,7% single took part in the study. From the quantitative research data, it was possible to analyze that women's perception about loneliness, in many aspects, matched the psychoanalytic theory. By analyzing the answers fond in this work, it has been perceived that most of the participants had a low sentiment of solitude (58,7%) and 41,3% classified themselves into a category ranging from high and medium one. In these groups, most women were either married or single, leading to the conclusion that, the younger the woman, the higher the tendency to search for relationship in order to scape from solitude. Also, is has been verified that this was true specially among married women. From these scores, 18 women were invited to take part into a diagnostic interview which consisted of six women in each group: two married, two single and two divorced from different ages, one of them being up to 29 and the other over 30 years old. The results found in these interviews were that all the women who presented a high feeling of loneliness have shown an inefficient adaptation to life, while those who presented a medium or low sentiment of solitude hardly presented this kind of behavior. Within the group of medium sentiment of solitude, three women presented inefficient adaptation to life and from the low sentiment of solitude group, only one participant presentd a slight one. Finally, we can conclude that loneliness if exaggerated, is not only painful but also indicates a great difficult of the individual to deal with his emotional and productive aspects leading him to need psychological help.